Long-term trends in food availability, food prices, and obesity in Samoa - Seiden, Andrew (2012)
OBJECTIVES: To describe long term food availability and prices from 1961 to 2007 and BMI trends from 1980–2010 in Samoa, and to contextualize these trends within political, economic, cultural, behavioral, and climatic influences. METHODS: National level data on food availability and pricing were obtained from the open access database FAO (http://faostat.fao.org). Data for Samoa were collected from annual food balance sheets available for the period 1961 to 2007. Mean BMI for Samoan men and women ages 35–44 years of age is reported from four different time periods, 1979–82, 1991, 2003, and 2010. RESULTS: Total energy availability increased substantially, by 47%, with more than 900 extra calories available per capita per day in 2007 than in 1961. Many of these extra calories are supplied by dietary fat, the availability of which rose by a proportionally greater amount, 73%. Availability of both meat and vegetable oils rose substantially. Poultry meat increased the most proportionally, from 10 to 117 kcal per capita per day. Coconut products, fruit and starchy root crops – all locally grown – showed little to no increase over this time. As import prices for poultry and mutton increased their availability decreased, but the availability of vegetable oils rose despite a rise in their price. Mean BMI for men and women ages 35–44 years rose 18% rise from 1980–2010. CONCLUSIONS: These long-term trends in food availability and prices, and the temporal pattern of BMI provide national level data for understanding the process of the nutrition transition in Samoa. Further work on consumer food prices, diet, food security and health is needed to further contextualize the transformation of the local food system in Samoa.